2022
DOI: 10.1080/14786419.2022.2071887
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of honokiol from Artemisia argyi and in vitro and in vivo investigation of its antifungal activity

Abstract: Extracts from plants used in Chinese medicine can be good sources of fungicides for agricultural applications. In this study, we separated and identified antifungal compounds from four traditional Chinese medicine extracts and evaluated their antifungal activities in vitro and in vivo. In vitro, honokiol extracted from Artemisia argyi showed broad-spectrum antimicrobial and mycelial inhibitory activity with EC50 in the range 3.56 -33.85 μg/mL against eight plant pathogens. q-PCR indicated that honokiol might i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this study, the inhibitory effects of seven phytochemicals against F. commune GUCCGF6 based on mycelial growth inhibition were studied with four phytochemicals found to have notable antifungal effects, and honokiol demonstrating the highest inhibition. Honokiol has been found to inhibit other fungi, such as Alternaria alternata and Rhizoctonia solani (Chen et al., 2019; Wang et al., 2022; Yan et al., 2020). The results of our pot study showed that honokiol, 2‐allylphenol, magnolol and carvacrol had significant control efficacy on rhizome rot of P. cyrtonema , but the antifungal mechanisms of these phytochemicals require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the inhibitory effects of seven phytochemicals against F. commune GUCCGF6 based on mycelial growth inhibition were studied with four phytochemicals found to have notable antifungal effects, and honokiol demonstrating the highest inhibition. Honokiol has been found to inhibit other fungi, such as Alternaria alternata and Rhizoctonia solani (Chen et al., 2019; Wang et al., 2022; Yan et al., 2020). The results of our pot study showed that honokiol, 2‐allylphenol, magnolol and carvacrol had significant control efficacy on rhizome rot of P. cyrtonema , but the antifungal mechanisms of these phytochemicals require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aldehydes, alcohols, and phenolic compounds have shown certain antifungal activities in previous studies (Xie et al 2017;Lee et al 2010). Phytochemicals have a low risk of resistance development and high antifungal activity, and are considered safe and environmentally friendly..Honokiol has been found to inhibit other fungi, such as Alternaria alternata and Rhizoctonia solani (Chen et al 2019;Yan et al 2020;Wang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…R. solanacearum RS10 was isolated from a diseased tobacco plant (Bai et al, 2016 ). The phytopathogenic fungi used in this study were Alternaria alternata, Phytophthora nicotianae, Botrytis cinerea, Fusarium oxysporum, Cucumber anthracnose , and Rhizoctonia cerealis (Xie et al, 2021 ; Wang et al, 2022 ). All strains were preserved in our laboratory and stored in 25% (v/v) glycerol at −80°C.…”
Section: Methodsmentioning
confidence: 99%